Myeloid Cell Hypoxia-Inducible Factors Promote Resolution of Inflammation in Experimental Colitis - Lin, Nan; Shay, Jessica E. S.; Xie, Hong; Lee, David S. M.; Skuli, Nicolas; Tang, Qiaosi; Zhou, Zilu; Azzam, Andrew; Meng, Hu; Wang, Haichao; FitzGerald, Garret A.; Simon, M. Celeste (Frontiers in Immunology, 2018)
Colonic tissues in Inflammatory Bowel Disease (IBD) patients exhibit oxygen deprivation and activation of hypoxia-inducible factor 1α and 2α (HIF-1α and HIF-2α), which mediate cellular adaptation to hypoxic stress. Notably, macrophages and neutrophils accumulate preferentially in hypoxic regions of the inflamed colon, suggesting that myeloid cell functions in colitis are HIF-dependent. By depleting ARNT (the obligate heterodimeric binding partner for both HIFα subunits) in a murine model, we demonstrate here that myeloid HIF signaling promotes the resolution of acute colitis. Specifically, myeloid pan-HIF deficiency exacerbates infiltration of pro-inflammatory neutrophils and monocytes into diseased tissue. Myeloid HIF ablation also hinders macrophage functional conversion to a protective, pro-resolving phenotype, and elevates gut serum amyloid A levels during the resolution phase of colitis. Therefore, myeloid cell HIF signaling is required for efficient resolution of inflammatory damage in colitis, implicating serum amyloid A in this process.